Audio Visual Assisted Problem Based Learning on Student Learning Outcomes in Class V Elementary Schools - Irawan, Pajar; Muhisom, Muhisom; Astuti, Nelly (Universitas Islam Negeri Raden Intan Lampung, 2024)
The aim of this research is to determine the effectiveness of implementing the Problem Based Learning (PBL) learning model assisted by audio-visual media on the learning outcomes of fifth grade elementary school students. The type of research used in this research is quantitative research. The research method uses a quasi- experimental design with a Nonequivalent Control Group Design. This experiment used two groups, namely the experimental and control groups. The population was 66 and the sample used was 22 class V A students and 22 class V B students. The sample was determined using a purposive sampling technique. Data was collected using tests in the form of multiple choice questions. Data were analyzed using normality tests, homogeneity tests, and hypothesis tests. The research results showed that the average posttest score for the experimental class was 82.5, while in the control class the average posttest score was 74. The results of hypothesis testing using the t test obtained a calculated t value of 8.781 and a t table of 2.021. It can be concluded that the Problem Based Learning (PBL) learning model assisted by audio visual media can be applied to improve learning outcomes in science subjects for students grade V in elementary schools.